The origins of violence : religion, history and genocide - Docker, John (Pluto Press, 2008)
Genocide is commonly understood to be a terrible aberration in human behavior, performed by evil, murderous regimes such as the Nazis and dictators like Suharto and Pinochet. John Docker argues that the roots of genocide go far deeper into human nature than most people realize. Genocide features widely in the Bible, the literature of ancient Greece and Rome, and debates about the Enlightenment. These texts are studied in depth to trace the origins of violence through time and across civilizations. Developing the groundbreaking work of Raphael Lemkin, who invented the term 'genocide', Docker guides us from the dawn of agricultural society, through classical civilization to the present, showing that violence between groups has been integral to all periods of history. This revealing book will be of great interest to those wishing to understand the roots of genocide and why it persists in the modern age.